“The Loneliness of the Incomprehensible Content”: Sergey Bobrov about Boris Pasternak - Anna Yu. Sergeeva-Klyatis (Studia Litterarum)
This is a publication of letters from Sergey Bobrov (1889–1971) to Eugeny and Elena Pasternak. The letters were written in the mid-1960s, shortly after the death of Boris Pasternak. They reflect Bobrov’s attempts to parse his archive as well as his reaction to the book entitled Pasternak by a French Slavist Jacqueline de Proyart published in 1964 by Gallimard. Exposing what he calls the myths created by the researcher, in his memoirs he discusses the youth of Boris Pasternak, talks about the probability of his baptism, his first steps in the field of poetry, and moves on to the discussion of his relationship with the “Centrifuge” group and the symbolist circle in general. Bobrov’s letters partly repeat what one might find in his published correspondence with Pasternak’s sisters but partly present an original contribution to the 20th century history of Russian culture.